The reduction of benzylbromide at Ag-Ni deposits prepared by galvanic replacement. (1st April 2016) - Vanrenterghem, B.; Papaderakis, A.; Sotiropoulos, S.; Tsiplakides, D.; Balomenou, S.; Bals, S.; Breugelmans, T.
Abstract: A two-step procedure was applied to prepare bimetallic Ag-Ni glassy carbon supported catalysts (Ag-Ni/GC). First Ni layers were prepared by means of electrodeposition in an aqueous deaerated nickel chloride + nickel sulfamate + boric acid solution. Second, the partial replacement of Ni layers by Ag was achieved upon immersion of the latter in solutions containing silver nitrate. Three different pretreatment protocols were used after preparation of the Ag/Ni deposits; as prepared, cathodised in alkali and scanned in acid. After the pretreatment the surface was characterised by means of spectroscopy techniques (scanning electron microscopy and energy dispersive x-ray) and electrochemically in an alkali NaOH solution through cyclic voltammetry (CV). Afterwards the modified electrodes were tested for the reduction of benzylbromide in acetonitrile solutions by using CV and were found to show improved activity compared to bulk Ag electrode. The highest activity towards benzylbromide reduction was observed for pre-cathodised Ag-Ni electrodes. A final stage of the research focuses on the development of a practical Ag/Ni foam catalyst for the reduction of benzylbromide. Due to the high electrochemical active surface area of Ag/Ni foam, a higher conversion of benzyl bromide was obtained in comparison with bulk Ag.